Critical role of chloride in organic ammonium spacer on the performance of Low-dimensional Ruddlesden-Popper perovskite solar cells - Chen, Haoran (2020)
Low-dimensional Ruddlesden-Popper (LDRP) perovskites attracted remarkable attention due to their technologically relevant intrinsic photo- and chemical-stability, suppressed ion migration, and ultralow self-doping effect over their 3D counterpart. The power conversion efficiency over 14% was recently achieved since the initial demonstration of LDRP perovskite solar cells (PSCs) in 2014. However, further improvements require a fundamental understanding on the components functionality in LDRP perovskites, e.g., bulky organic ammonium spacer and halogen ions, which are critical for designing efficient LDRP PSCs. Here, we report the critical role of the chloride that are derived from halogenated organic ammonium salts on the LDRP perovskite film crystallization, growth, opto-electric properties, and device performance. We found that the expected improvements in perovskite morphology with increased grain size, enhanced crystallinity, and uniform and smooth surface were revealed no matter which introduced chloride either by bulky organic ammonium or methyl ammonium salts. We also unambiguously demonstrated that photocurrent and photovoltage of LDRP PSCs are highly related to the position of chloride on organic ammonium salts. Moreover, the films and devices maintain excellent stability by the introduction of chloride due to the excellent film quality. The resulting LDRP PSCs exhibited best efficiency of 12.78%, which is two times enhancement compared to all iodide-contained device (6.52%) commonly used in previous reports. These findings demonstrated that chloride plays a significant role in LDRP perovskite and detected a key parameter for the development of future LDRP perovskite absorbers and relevant optoelectronic devices.